Analisa Pemanfaatan Learning Management System Schoology Menggunakan HOT Fit Model terhadap Pembelajaran di Masa Pandemi Covid 19 - Mujianto, Ahmad Heru; Mashuri, Chamdan; Permadi, Ginanjar Setyo; Wiratsongko, Radityo (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2022)
The Covid-19 pandemic in Indonesia has resulted in face-to-face learning methods having to be replaced with online learning. Several e-learning applications can be used as online learning media, including the learning management system (LMS) Schoology. This study aims to analyze the benefits of LMS Schoology for algorithm courses with the HOT Fit model framework which analyzes the system in terms of system quality, information quality, service quality, system use, user satisfaction, benefits and organization. Based on the analysis, it was found that LMS Schoology was able to provide benefits and help students in online learning of algorithms and programming, this was indicated by the average respondents' answers from 23 questions that had a value of 3, which means that respondents answered Agree regarding the benefits obtained. Although overall LMS Schoology is said to be good for use in learning algorithms, it is still necessary to pay attention to several variables that have a value of respondent dissatisfaction, so that this deficiency can be improved to improve LMS Schoology, especially in terms of ease of access and use of the system which still has a value of user dissatisfaction